2022
DOI: 10.1038/s41586-022-04984-8
|View full text |Cite
|
Sign up to set email alerts
|

PI3K drives the de novo synthesis of coenzyme A from vitamin B5

Abstract: In response to hormones and growth factors, the class I phosphoinositide-3-kinase (PI3K) signalling network functions as a major regulator of metabolism and growth, governing cellular nutrient uptake, energy generation, reducing cofactor production and macromolecule biosynthesis1. Many of the driver mutations in cancer with the highest recurrence, including in receptor tyrosine kinases, Ras, PTEN and PI3K, pathologically activate PI3K signalling2,3. However, our understanding of the core metabolic program cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 62 publications
0
40
0
1
Order By: Relevance
“…7d) . PANK4 dephosphorylates 4’-phosphopantetheine, an intermediate metabolite of CoA biosynthesis, to antagonize CoA biosynthesis 7 . We confirmed that genetic disruption of PANK4 conferred a competitive growth advantage under selective pressure from CBP/p300 HAT inhibition and clonal expansions of the MOLM-13 cells with PANK4 knockouts displayed diminished sensitivity to CBP/p300 HAT inhibition by A-485 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7d) . PANK4 dephosphorylates 4’-phosphopantetheine, an intermediate metabolite of CoA biosynthesis, to antagonize CoA biosynthesis 7 . We confirmed that genetic disruption of PANK4 conferred a competitive growth advantage under selective pressure from CBP/p300 HAT inhibition and clonal expansions of the MOLM-13 cells with PANK4 knockouts displayed diminished sensitivity to CBP/p300 HAT inhibition by A-485 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We further validated these results using a genome-scale CRISPR/Cas9 loss-of-function genetic modifier screen, which identified additional gene-drug interactions between HAT inhibitors and the CoA biosynthetic pathway. Top hits from the screen included the phosphatase, PANK4 , which negatively regulates CoA production and therefore suppresses sensitivity to HAT inhibition upon knockout 7 , as well as the pantothenate transporter, SLC5A6 8 , which enhances sensitivity. Altogether, this work uncovers CoA plasticity as an unexpected but potentially class-wide liability of anti-cancer HAT inhibitors and will therefore buoy future efforts to optimize the efficacy of this new form of targeted therapy.…”
mentioning
confidence: 99%
“…Pantothenate kinases, a family of four evolutionarily conserved proteins, regulate the de-novo CoA biosynthesis in prokaryotes as well as eukaryotes [ 5 ]. The family of PANKs constitutes four catalytically active kinases: nuclear PANK1α and cytosolic PANK1β (both encoded by PANK1 ); mitochondrial (intermembrane space) PANK2; cytosolic PANK3; and a phosphatase—cytosolic PANK4 [ 6 , 7 ]. As the rate-limiting enzymes of the pathway, PANK1, 2, and 3 phosphorylate pantothenic acid (vitamin B 5 ), which is converted into CoA in a series of four evolutionarily conserved enzymatic reactions, while PANK4 negatively regulates CoA synthesis by dephosphorylation of the pathway metabolites [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The family of PANKs constitutes four catalytically active kinases: nuclear PANK1α and cytosolic PANK1β (both encoded by PANK1 ); mitochondrial (intermembrane space) PANK2; cytosolic PANK3; and a phosphatase—cytosolic PANK4 [ 6 , 7 ]. As the rate-limiting enzymes of the pathway, PANK1, 2, and 3 phosphorylate pantothenic acid (vitamin B 5 ), which is converted into CoA in a series of four evolutionarily conserved enzymatic reactions, while PANK4 negatively regulates CoA synthesis by dephosphorylation of the pathway metabolites [ 6 , 7 , 8 ]. PANK isoforms are also differentially expressed and regulated, enabling these proteins to sense and maintain the levels of CoA and its thioesters differentially in a specific cellular compartment [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In prokaryotes as well as higher eukaryotes, denovo CoA synthesis occurs from pantothenate, with the first and rate limiting step catalyzed by the pantothenate kinase (PANK) family of enzymes (Figure 1B) (22,23). Three PANK enzymes catalyze the conversion of pantothenate to 4'-phosphopantothenate (PANK1, 2, and 3), with PANK4 retaining phosphatase activity that is suggested to be critical in constraining cellular CoA concentration (22)(23)(24)(25). Our investigations on CoA biosynthesis as a potential targetable vulnerability in cancers led us to assess whether genetic manipulation of the pantothenate kinases PANK 1, 2 and 3, as the key regulatory enzymes of de-novo CoA biosynthesis in prokaryotes and eukaryotes, could impact cancer cell viability.…”
Section: Introductionmentioning
confidence: 99%